Problematika Perlindungan Hukum terhadap Produk Indikasi Geografis - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Geographical Indications are legal protections that are regulated in TRIPs on goods or products based on the reputation, quality and characteristics of each region. IG is a separate Intellectual Property Rights which is different from other Intellectual Property Rights because IG can only be registered as a joint / communal right. Geographical Indications are regulated in one Act with a mark, namely Law Number 20 Year 2016 concerning Trademarks and Geographical Indications. IG is a communal right so that in the implementation of its protection it can cause various problems, both in terms of product marketing by external parties and by the IG owner community it self. In terms of supervision it can also cause problems because of the connection with the difficulty of conducting supervision because it involves many individuals with different interests and characters. IG arrangements must be sufficient to support local economic development efforts and even be able to compete globally.